2017
DOI: 10.5387/fms.2017-04
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced harmonic endoscopic ultrasonography in gallbladder cancer and pancreatic cancer

Abstract: Endoscopic ultrasonography (EUS) plays a major role in diagnosing gallbladder (GB) cancer and pancreatic cancer (PC). In cases of GB cancer, EUS allows for precise observations of morphology and wall layers. However, proficiency is required for the morphologic diagnosis of GB tumors. Therefore, contrast -enhanced harmonic EUS (CH -EUS) began to be performed to diagnose GB lesions. CH -EUS enables real -time observation of the hemodynamics of GB tumors. The enhanced patterns generated by CH -EUS improve precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Apart from the pathological immunohistochemical examinations, contrast-enhanced ultrasonography has differential clinical significance (38). Case reports using contrast-enhanced ultrasonography have revealed that biliary sludge is not enhanced (39) .In these case reports, the gallbladder polyp was enhanced with grape-like fine pedicles and the three-layer structure of gallbladder wall was clear (40) .For adenomyosis of the gallbladder, unenhanced vesiculoid echocardiography was observed and the inner and serous membranes of the gallbladder were intact (41). Gallbladder adenoma resulted in delayed enhancement that was identifiable by 'fast in and slow out' through the complete three-layer structure of the gallbladder wall (38).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Apart from the pathological immunohistochemical examinations, contrast-enhanced ultrasonography has differential clinical significance (38). Case reports using contrast-enhanced ultrasonography have revealed that biliary sludge is not enhanced (39) .In these case reports, the gallbladder polyp was enhanced with grape-like fine pedicles and the three-layer structure of gallbladder wall was clear (40) .For adenomyosis of the gallbladder, unenhanced vesiculoid echocardiography was observed and the inner and serous membranes of the gallbladder were intact (41). Gallbladder adenoma resulted in delayed enhancement that was identifiable by 'fast in and slow out' through the complete three-layer structure of the gallbladder wall (38).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…53,54 EUS-FNAB under CEH-EUS may improve the diagnostic accuracy and adequacy with fewer needle passes. [55][56][57][58]…”
Section: Targeting Under Contrast-enhanced Harmonic Eusmentioning
confidence: 99%
“…It should be clear that asymptomatic patients who can be observed for a long time should not be blindly operated on to remove gallbladder; similarly, it should not be free to preserve gallbladder and stone [18]. Cholecystectomy or cholecystolithotomy should be carefully selected, and excessive treatment should be vigilant [19,20]. As for whether long-term observation of asymptomatic gallstones will lead to delayed treatment of gallbladder carcinogenic, this is another aspect of the problem [21].…”
Section: Citationmentioning
confidence: 99%